Factors affecting inter-ethnic relation at workplace / Noor Nabihah Mothar - Mothar, Noor Nabihah (Faculty of Business and Management, 2018)
The purpose of this research is to study on the factors affecting inter-ethnic relation at the workplace. This is because based on past studies, it has shown that many Malaysians are racists of have a slight shades of racism. It then causes discrimination at workplace which are a troubling issue as the productivity of the company are jeopardized which could affect the economy of the country. There are four independent variables that has been identified for this study which are education background, family and peer influences, religion background and political influence. This research was conducted among the employees around the Klang Valley area. The information that has been gathered was distributed among 100 respondents by using quota sampling technique. All 100 respondents were managed be collected and answered by the respondents. The results of the data was analyzed and summarized using the Statistical Package Social Science (SPSS V22). The statistical analysis were demographic profiles of the respondents, correlations analysis and multiple regression. The results has shown out of four independent variables, only two independent variables which are religion background and political influence significant to the factors affecting inter-ethnic relation at the workplace. This study may help in combating racism and discrimination that is faced by Malaysians employees. Suggestions for future research are also mentioned in the study.